2002
DOI: 10.1007/s00417-002-0466-y
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal blood pressure reduction: effect on retrobulbar hemodynamics in glaucoma

Abstract: In patients with non-progressing glaucoma there was no evidence of cerebral or retrobulbar hemodynamic abnormalities during nocturnal BP dips. Posterior ciliary arterial blood flow velocities were similar in glaucoma patients and controls during nocturnal BP dips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 21 publications
2
27
1
Order By: Relevance
“…They found that maximal posture-corrected nocturnal BP reductions were similar (~10%) in patients and controls, suggesting that in patients with nonprogressing glaucoma, there was no evidence of cerebral or retrobulbar hemodynamic abnormalities during nocturnal BP dips. 86 Although few conflicting data remain, the majority of studies point to a correlation between nocturnal hypotension and glaucoma.…”
Section: Nocturnal Hypotensionmentioning
confidence: 98%
See 2 more Smart Citations
“…They found that maximal posture-corrected nocturnal BP reductions were similar (~10%) in patients and controls, suggesting that in patients with nonprogressing glaucoma, there was no evidence of cerebral or retrobulbar hemodynamic abnormalities during nocturnal BP dips. 86 Although few conflicting data remain, the majority of studies point to a correlation between nocturnal hypotension and glaucoma.…”
Section: Nocturnal Hypotensionmentioning
confidence: 98%
“…85 Few studies, however, have attempted to investigate ocular blood flow at night in glaucoma patients. Harris et al 86 investigated whether reductions in nocturnal BP are linked to retrobulbar blood flow perturbations in glaucoma patients. They found that maximal posture-corrected nocturnal BP reductions were similar (~10%) in patients and controls, suggesting that in patients with nonprogressing glaucoma, there was no evidence of cerebral or retrobulbar hemodynamic abnormalities during nocturnal BP dips.…”
Section: Nocturnal Hypotensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of nocturnal blood pressure reduction on retrobulbar hemodynamics in glaucoma The authors' [2] conclusions are based on recording BP and performing color Doppler imaging (CDI) and transcranial Doppler (TCD) in 15 patients with nonprogressing glaucoma and 15 control subjects who were first studied in the evening ("baseline") and then during the night. One must critically evaluate their study design for finding out the validity of "nocturnal arterial hypotension" and its effects on retrobulbar hemodynamics.…”
Section: Sohan Singh Hayrehmentioning
confidence: 99%
“…Dear Professor Krieglstein: I was interested to read the paper by Harris and colleagues [2]; they claim they have evaluated the effect of nocturnal fall of blood pressure (BP) on retrobulbar hemodynamics in non-progressing glaucoma. The authors' conclusion was that in patients with nonprogressing glaucoma, "nocturnal arterial BP reductions are neither abnormally large nor associated with changes in retrobulbar arterial or middle cerebral arterial flow velocities," and that "there was no evidence of cerebral or retrobulbar hemodynamics abnormalities during nocturnal BP dips."…”
mentioning
confidence: 99%